INTEGRATION OF GREEN INNOVATIONS INTO HIGHER EDUCATION MARKETING STRATEGIES (Marketing Jurnali, 2025)
This paper explores the integration of green innovations into the marketing strategies of higher education institutions (HEIs). As sustainability becomes a global priority, universities are expected not only to provide quality education but also to demonstrate responsibility toward environmental and social challenges. Green innovations—such as eco-friendly infrastructure, renewable energy systems, waste reduction programs, and sustainability-oriented curricula—are increasingly adopted by universities as both operational improvements and marketing tools. Their effective integration enhances institutional reputation, attracts environmentally conscious students, strengthens stakeholder trust, and fosters long-term competitiveness in a global education market. However, challenges such as financial limitations, communication gaps, and risks of greenwashing remain significant barriers. By analyzing existing literature and practical examples, the study emphasizes that authentic, transparent, and strategic communication of green innovations can position universities as leaders in sustainable development while achieving competitive advantage.